New developments in psychological choice modeling - Soete, Geert de.; Feger, Hubert; Klauer, Karl C.; ScienceDirect eBooks (Amsterdam ; New York : North-Holland ; New York, N.Y., U.S.A. : Distributors for the United States and Canada, Elsevier Science Pub., 1989)
A selection of 15 papers on choice modeling are presented in this volume. These papers result from research in the social and behavioral sciences and in economics. The models, some deterministic, some probabilistic, represent recent developments in the tradition of Thurstone's Law of Comparative Judgement, Coombs' unfolding theory and multidimensional scaling. The theoretical contributions and several applications to voting behaviour, consumer research and preference rankings show the important progress made in psychological choice modeling during the last few years.
Testing probabilistic choice models / P.M. Bossuyt & E.E. Roskam -- On the axiomatic foundations of unfolding, with an application to political party references of German voters / B. Orth -- Unfolding and consensus ranking : a prestige ladder for technical occupations / R. van Blokland-Vogelesang -- Unfolding the German political parties : a description and application of multiple unidimensional unfolding / W.H. van Schuur -- Probabilistic multidimensional scaling models for analyzing consumer choice behavior / W.S. DeSarbo, G. De Soete, and K. Jedidi -- Probabilistic choice behavior models and their combination with additional tools needed for applications to marketing / W. Gaul.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Choice (Psychology) -- Mathematical models; Choice (Psychology) -- Research -- Statistical methods; Choice Behavior; Models, Psychological; SELF-HELP -- Motivational & Inspirational; Keuzegedrag; Schaalmethoden; Psychologie; Mathematisches Modell; Aufsatzsammlung; Entscheidungsverhalten; Kind; Entscheidung; Modellierung; Wahlmöglichkeit; Modell; Choice (Psychology) -- Mathematical models; Decision making; Electronic books